School Supervision And Workload On Teacher Performance: The Mediating Role Of Self-Efficacy And Organizational Commitment In JSIT Elementary Schools, Riau Province - Amirul Hidayat; Ahmad Subagyo; Muhammad Yusuf (CV. Kayaswara, 2026)
Teacher performance is factor determinant quality education , but Still become challenges in various context , including in the Integrated Islamic Elementary School (SDIT) Network Integrated Islamic School (JSIT) of Riau Province . Teachers face improvement demands professional from pressure supervision and burden work that influences performance they . Research This aim For analyze influence direct and indirect direct from supervision supervisor school and workload Work to teacher performance , with mediated by efficacy self and commitment teacher organization . Approach quantitative associative used in study this . Sample A total of 190 teachers were selected through proportional random sampling from population of 744 SDIT teachers in Riau. Data collected through questionnaire standardized and analyzed use Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS . Findings disclose that supervision supervisor school and workload Work own influence direct significant positive​ to teacher performance . More far , efficacy self and commitment organization found mediate in a way significant connection between variables independent and teacher performance . Research This conclude that improvement quality supervision supervisors and management burden effective teacher work is very important For increase performance , where the impact strengthened in a way significant through development efficacy self and commitment teacher organization . Findings This give contribution theoretical for management models education as well as implications practical for JSIT administrators and creators policy in designing sustainable teacher development programs .